Darshan Rajpal Abhaichand - Rajpal Abhaichand, Darshan (2015)
This research study looks at the factors affecting a nurse’s motivation using qualitative research. It studies nurses’ experience of job satisfaction and their intention to remain in their current roles in an Indian context. It presents the different studies on nurses’ satisfaction in developing countries and compares them to research done by him in India. The research will investigate the factors affecting nurses’ work satisfaction in India. A semi- structured interview was chosen as the qualitative approach to be used to obtain in-depth data. 10 nurses took part in the interview and the data gathered from the interview transcripts were analysed. The findings showed that while some of Herzberg’s motivating factors and hygiene factors existed at the hospital others didn’t. There existed factors that lead to nurses quitting their jobs. The findings revealed that salary played a very important role in a nurse’s satisfaction at work. However there were other factors or lack thereof that affected the job satisfaction of nurses.